Screening for a Single JAK2(p.V617F)Mutation Allele in Suspected Patients with Myeloproliferative Neoplasms (MPN) at HIWA Hospital - Rashid, Nawshirwan G.; Tawfiq, Shwan Ali; Karim, Dana O.; Safar, Banaz M.; Ahmad, Nihayat A.; Nore, Beston F.; Rasheed, Mariwan K.; Rashid, Ban M.; Mohammed, Mohammed O.; Khoshnaw, Najmaddin S.H. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Detection and diagnosis of the myeloproliferative neoplasms (MPNs) are difficult to predict without screening for genetic causes, includingpolycythemia vera (PV), essential thrombocythemia (ET), primary myelofibrosis (PMF) and chronic myeloid leukemia (CML). A novel mutation in the Janus kinase 2 (JAK2) gene has been described as a genetic marker prime for all four-types of MPNs.The specific c.1851G>T (p.V617F) mutation leads to constitutively activetyrosine kinase activity of JAK2, inducing downstream JAK/STAT pathways of cytokine signaling. The existence of the JAK2(c.1851G>T; p.V617F) mutation has a clinical importance in diagnosis of MPNs. In this study, amplification refractory mutation system (ARMS) assay for a specific mutation detection was utilized, which is an Allele Specific Oligonucleotide (ASO) based multiplex PCR method. Genomic DNA samples were isolated from total blood samples from suspected MPN patients, who visited Hiwa hospital (the main teaching hospital for cancer in Sulaimani city). The aim of this study was to screen for JAK2 mutation c.1851G>T (p.V617F) on a group of suspected patients for MPNs (100 patients). The result shows that 65% of patients had indeed c.1851G>T mutation and the rest 35% of patients were normal for the mutation. In this study, we have shown the ARMS assay method to be quick, simple, cheap, reliable, and gives sufficient sensitivity for positive detection compatible forclinical diagnostic purposes. Therefore, the assay can be used for early diagnosis of MPNsin diagnostic laboratories with limited resources, such as in our health care system in our locality.
Keywords: Detection and diagnosis of the myeloproliferative neoplasms MPNs are difficult to predict without screening for genetic causes; includingpolycythemia vera PV; essential thrombocythemia ET; primary myelofibrosis PMF and chronic myeloid leukemia CML A novel mutation in the Janus kinase 2 JAK2 gene has been described as a genetic marker prime for all fourtypes of MPNsThe specific c1851GT pV617F mutation leads to constitutively activetyrosine kinase activity of JAK2; inducing downstream JAKSTAT pathways of cytokine signaling The existence of the JAK2c1851GT pV617F mutation has a clinical importance in diagnosis of MPNs In this study; amplification refractory mutation system ARMS assay for a specific mutation detection was utilized; which is an Allele Specific Oligonucleotide ASO based multiplex PCR method Genomic DNA samples were isolated from total blood samples from suspected MPN patients; who visited Hiwa hospital the main teaching hospital for cancer in Sulaimani city The aim of this study was to screen for JAK2 mutation c1851GT pV617F on a group of suspected patients for MPNs 100 patients The result shows that 65 of patients had indeed c1851GT mutation and the rest 35 of patients were normal for the mutation In this study; we have shown the ARMS assay method to be quick; simple; cheap; reliable; and gives sufficient sensitivity for positive detection compatible forclinical diagnostic purposes Therefore; the assay can be used for early diagnosis of MPNsin diagnostic laboratories with limited resources; such as in our health care system in our locality